On the detection of the level of attention in an orchestra through head movements. (22nd December 2014) - Gnecco, Giorgio; Glowinski, Donald; Camurri, Antonio; Sanguineti, Marcello
Results from a study of non-verbal social signals in an orchestra are presented. Music is chosen as an example of interactive and social activity, where non-verbal communication plays a fundamental role. The orchestra is adopted as a social group with a clear leader (the conductor) of two groups of musicians (the first and second violin sections). It is shown how a reduced set of simple movement features – head movements – can be used to measure the levels of attention of the musicians with respect to the conductor and the music stand under various conditions (different conductors/pieces/sections of the same piece).